2011
DOI: 10.1590/s0100-29452011000500017
|View full text |Cite
|
Sign up to set email alerts
|

Progressos na viticultura brasileira

Abstract: RESUMO -A viticultura brasileira nasceu com a chegada dos colonizadores portugueses, tornando-se uma atividade comercial a partir do início do século XX. Houve absoluto predomínio do cultivo de uvas americanas até meados do século XX, quando se iniciou o plantio de videiras europeias. Até a década de 1960, a viticultura brasileira ficou limitada às regiões Sul e Sudeste. A partir daí, a uva alastrou-se como alternativa econômica em diversas regiões tropicais do País e ganhou nova dimensão nas zonas temperadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
38

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 2 publications
1
45
0
38
Order By: Relevance
“…According to Gris et al (2013), anthocyanins are effective antioxidants, and the anthocyanin composition of grapes varies according to species, cultivar, ripeness, seasonal conditions and solar radiation levels. Cabrita et al (2003) found similar values in red wine produced with Trincadeira grapes, i.e. total phenolics content of 1568.0 mg EC.…”
Section: Phenolic Compounds Flavonoids Anthocyanins and Antioxidantsupporting
confidence: 69%
See 1 more Smart Citation
“…According to Gris et al (2013), anthocyanins are effective antioxidants, and the anthocyanin composition of grapes varies according to species, cultivar, ripeness, seasonal conditions and solar radiation levels. Cabrita et al (2003) found similar values in red wine produced with Trincadeira grapes, i.e. total phenolics content of 1568.0 mg EC.…”
Section: Phenolic Compounds Flavonoids Anthocyanins and Antioxidantsupporting
confidence: 69%
“…The fact that the IsSC wine has a less intense and less reddish colour than the other wines from the southern region may be explained by differences in the wine production process, as wine colour also depends on other factors such as grape variety. The Isabella grape has less colouring than is desirable for wines and often needs to be cut with other species that confer colour (Camargo et al, 2011).…”
Section: Colour Evaluationmentioning
confidence: 99%
“…According to data from the Food and Agriculture Organization (2010), Brazil occupies the 20 th position in terms of world production of grapes. In 2012, data show that the annual production of grapes in Brazil ranged from 1.3 and 1.4 million tons/year (Camargo et al, 2011;Instituto Brasileiro de Geografia e Estatística (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dados levantados pela Emater/RS, todavia, identificaram um aumento de 90 hectares destinados à produção de uvas em 2005 para 517 hectares em 2011. Isso corresponde a um aumento de 1000 para 7000 toneladas destinadas ao consumo in natura e à produção de sucos e vinhos (Camargo et al, 2011).…”
Section: Introductionunclassified